MEIOBENTHIC COMMUNITY OF SUNGAI PULAI SEAGRASS BED, MALAYSIA - Kassim, Zaleha; Diyana, Farah; Fathi, Mohd; Ahmad, Amirudin (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2008)
Meiobenthos inhabiting the seagrass bed of Sungai Pulai estuary, Johor, was studied for the differences in community structure. Sampling was carried out using a hand corer during the lowest tide in December 2006. Three stations were chosen that were located at the upper estuary, lower estuary and at the sea area. Cluster analysis dendrogram of Bray-Curtis similarity showed the similarity level at about 70-75% and from the MDS plot, it is found that communities at upper estuary were separated from those at lower estuary and at sea. The differences in environmental setting were thought as the significant contributor to the distribution of meiobenthos among the stations.